Hereditary Transthyretin Amyloidosis Polyneuropathy - Qarni, Taha; Moshe-Lilie, Orly; Kaku, Michelle C.; Karam, Chafic (Seminars in Neurology, 2024)
In the last decade, we have witnessed dramatic improvements in the diagnosis, workup, management, and monitoring of patients with hereditary transthyretin amyloidosis (ATTRv). Updated imaging techniques (e.g., 99mTc-PYP scan) are increasingly being used in place of tissue biopsies for confirmation of disease. Novel treatments now include antisense oligonucleotide and RNA interference drugs, whereas new applications such as CRISPR and amyloid antibodies are being studied for potential use in the future. These treatments have dramatically improved quality of life and increased survival in patients with ATTRv. Despite these breakthroughs, many challenges remain. Some of these challenges include early recognition and diagnosis of ATTRv, monitoring and initiation of treatment in asymptomatic or paucisymptomatic carriers, adequate treatment in people with mixed phenotype (i.e., cardiac and neurological), and the emergence of new phenotypes in people living longer with the disease (i.e., central nervous system and ocular complications). Research in those areas of deficit is ongoing, and in the future, we may have preventive therapies, better biomarkers, more efficient therapies for organs that we cannot currently target, and enhanced diagnostic techniques with the help of novel imaging techniques and artificial intelligence. In this review, we will summarize the current knowledge about polyneuropathy related to ATTRv and its management, discuss methods to improve early diagnosis and monitoring, and discuss emerging trends.
Keywords: ATTRv amyloidosis; familial amyloid polyneuropathy; cardiac amyloidosis; hereditary transthyretin amyloidosis